STRENGTH CHARACTERISTICS OF GEOPOLYMER CONCRETE INCORPORATING POLYPROPYLENE FIBRE UNDER FIRE CONDITION - AZBAH, ABDULLAH; TASHAN , JAWDAT (Journal of Duhok University, 2023)
The widespread use of concrete in construction is driven by its adaptability, strength, and durability. However, the environmental repercussions associated with conventional concrete made from ordinary Portland cement (OPC) have raised concerns due to resource depletion, energy consumption, and greenhouse gas emissions. This study presents the results of compressive strength tests performed on multiple concrete mixes that utilize eco-friendly  geopolymer technology and polypropylene fibres that were subjected to elevated temperatures. The study investigated a total of six concrete mix designs that utilize ground granulated blast furnace slag (GGBFS) and fly ash (FA) as a total replacement for conventional ordinary Portland cement (OPC). Sodium Hydroxide was used as an activator with identical proportions between the mixes. The results showed that the inclusion of 1 kg/m3 of PP fibres had no significant effect on compressive strength. The results reveal a notable increase in compressive strength of over 50% when incorporating GGBFS and PP fibres. Upon exposure to elevated temperatures, geopolymer-based mixtures exhibited significant compressive strength reduction, with certain samples experiencing nearly 70% strength loss. Future research should focus on devising strategies to mitigate these effects and enhance fire resistance for practical applications.